2019
DOI: 10.1029/2019ms001684
|View full text |Cite
|
Sign up to set email alerts
|

Exploring a Lower‐Resolution Physics Grid in CAM‐SE‐CSLAM

Abstract: This paper describes the implementation of a coarser-resolution physics grid into the Community Atmosphere Model (CAM), containing 5 9 fewer grid columns than the dynamics grid. The dry dynamics is represented by the spectral element dynamical core, and tracer transport is computed using the Conservative Semi-Lagrangian Finite Volume Method (CAM-SE-CSLAM). Algorithms are presented that map fields between the dynamics and physics grids while maintaining numerical properties ideal for atmospheric simulations suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 42 publications
5
28
0
Order By: Relevance
“…The preferred way to address the grid imprinting is to completely remove or mask the inhomogeneity that is inherent between the nodes of the GLL grid. Herrington, Lauritzen, Reed, et al () and Herrington, Lauritzen, Taylor, et al () did this by moving the physics calculations to a quasi‐equal‐area finite volume grid. We have implemented a scheme inspired by their work that uses a 2 × 2 grid of finite volume cells for each spectral element and an interpolation method that does not require information from neighboring elements.…”
Section: Discussionmentioning
confidence: 99%
“…The preferred way to address the grid imprinting is to completely remove or mask the inhomogeneity that is inherent between the nodes of the GLL grid. Herrington, Lauritzen, Reed, et al () and Herrington, Lauritzen, Taylor, et al () did this by moving the physics calculations to a quasi‐equal‐area finite volume grid. We have implemented a scheme inspired by their work that uses a 2 × 2 grid of finite volume cells for each spectral element and an interpolation method that does not require information from neighboring elements.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is suggested that the overwhelming support for the h = 1/3 exponent in the second‐order structure function is only relevant for horizontal scales of the order of 100 km and less (Lindborg, 1999; Cho and Lindborg, 2001). This mesoscale regime is only marginally resolved in the highest resolution simulation, Δx=27.8 km ( ne 120), since CAM‐SE‐CSLAM has an effective resolution in the range of 5–10Δx (Herrington et al ., 2019). The nonexistence of h = 1/3 in the Δx=27.8 km simulation is verified through analyzing the slope of the kinetic energy spectrum β, which is in duality with the second‐order structure function through the Weiner–Khinchine theorem.…”
Section: Discussionmentioning
confidence: 99%
“…The coupled system, referred to as CAM‐SE‐CSLAM, conserves energy and mass and preserves linear correlations between two reactive species to within machine precision (Herrington et al ., 2018). A coarser physics grid, containing 5/9 fewer degrees of freedom than the dynamical core grid, is also available as part of the CAM‐SE‐CSLAM package (Herrington et al ., 2019). This lower‐resolution physics grid is used in this study, but only as a member of a perturbed parameter ensemble and not in the control convergence experiment.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is not uncommon to apply different resolutions for different components of a numerical model. For example, Herrington et al (2019) showed that a high-resolution dynamical core using low-resolution parameterizations generates satisfactory results.…”
Section: Introductionmentioning
confidence: 99%